2009
DOI: 10.1299/jmmp.3.943
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Oil Palm Empty Fruit Bunch Fiber

Abstract: In tropical countries such as Indonesia and Malaysia, the empty fruit bunches are wastes of the oil palm industry. The wastes are abundantly available and has reached a level that severely threats the environment. Therefore, it is a great need to find useful applications of those waste materials; but firstly, the mechanical properties of the EFB fiber should be quantified. In this work, a small tensile test machine is manufactured, and the tensile test is performed on the EFB fibers. The results show that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 4 publications
1
25
1
1
Order By: Relevance
“…The SEM images of the cross-section area of the fibres (Fig. 3d) show no large voids or openings, which is consistent with the findings by Gunawan et al (2009).…”
Section: Tensile Testssupporting
confidence: 90%
See 3 more Smart Citations
“…The SEM images of the cross-section area of the fibres (Fig. 3d) show no large voids or openings, which is consistent with the findings by Gunawan et al (2009).…”
Section: Tensile Testssupporting
confidence: 90%
“…This value was smaller than the elastic moduli reported in previous work (1.7 GPa by Yusoff et al (2009) and 5 GPa by Gunawan et al (2009)) and could be due to planting condition and geometry differences of the samples. Yusoff et al (2009) and Gunawan et al (2009) reported increases of elastic modulus with reduction of the diameter of the fibres. Gunawan et al (2009) showed that this is due to large voids or openings in the cross section of OPEFB which cause a non-uniform cross section area.…”
Section: Standard Deviation Denoted In Parenthesescontrasting
confidence: 77%
See 2 more Smart Citations
“…1). The spots on the composite films were silica bodies embedded in the EFB pulp fibers (Gunawan et al 2009;Harsono et al 2016). Hence, more EFB pulp added into the seaweed matrix resulted in more black spots on the surface of the film.…”
Section: Discussionmentioning
confidence: 99%